Sphingosine 1-Phosphate in Malaria Pathogenesis and Its Implication in Therapeutic Opportunities - Dhangadamajhi, Gunanidhi; Singh, Shailja (Frontiers in Cellular and Infection Microbiology, 2020)
Sphingosine 1-Phosphate (S1P), a bioactive lipid intermediate in the sphingolipid metabolism exist in two pools, intracellular and extracellular each with different function. The circulating extracellular pool, specifically the plasma S1P has been shown important in regulating various physiological processes related to malaria pathogenesis in recent years. Although blood cells (red blood cells and platelets), vascular endothelial cells and hepatocytes are considered as the important sources of plasma S1P, their extent of contribution is still debated. The red blood cells (RBCs) and platelets serve as major repository of intracellular S1P due to lack, or low activity of S1P degrading enzymes, however, contribution of platelets towards maintaining plasma S1P is shown negligible under normal condition. Substantial evidences suggest platelets loss during falciparum infection as contributing factor for severe malaria. However, whether platelets function as a source for plasma S1P in malaria needs to be examined experimentally. RBC being the preferential site for parasite seclusion, and having the ability of trans-cellular S1P transportation to EC upon tight cell-cell contact, might play critical role in differential S1P distribution and parasite growth. In the present review, we have summarized the significance of both the S1P pools in the context of malaria, and how RBC content of S1P can be channelized in better ways for its possible implication in therapeutic opportunities to control malaria.